Educational Financing Management Based on Madrasah Self-Reliance at MTs Al-Amien, Kediri City - Faza, Pryzam Putri; Weny, Siska Yulia (Proceeding International Conference on Education, 2025)
Educational financing is one of the key factors in ensuring the continuity and quality of education. Amid government budget efficiency policies, educational institutions—particularly independent and growing private madrasahs such as MTs Al-Amien in Kediri City—are required to manage their finances effectively and efficiently. This study aims to explore the processes of: (1) Planning, (2) Implementation, and (3) Evaluation of educational financing based on madrasah self-reliance at MTs Al-Amien. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The findings show that financing management is carried out systematically and responsibly, starting with the establishment of a Quality Assurance Team by the principal. Budget planning is prepared through the RKAM, guided by the EDM, and involves various stakeholders within the madrasah. The main sources of funding include regular government BOS funds, parental contributions, and non-routine independent funding through external collaboration. Budget implementation prioritizes essential needs, aligns with available funds, and follows strict disbursement procedures. Both manual and digital bookkeeping systems are applied. Financial evaluations are conducted periodically in line with the budget cycle as a form of accountability and to improve financial management quality. All elements of the madrasah actively participate in the evaluation process. Financial constraints are addressed by seeking alternative support through proposal submissions to local or provincial governments and collaborating with PT Taspen. The evaluation results are used as the basis for future budgeting.